2008
DOI: 10.1111/j.1467-7687.2008.00742.x
|View full text |Cite
|
Sign up to set email alerts
|

Early bilingualism enhances mechanisms of false‐belief reasoning

Abstract: In their first years, children's understanding of mental states seems to improve dramatically, but the mechanisms underlying these changes are still unclear. Such 'theory of mind' (ToM) abilities may arise during development, or have an innate basis, developmental changes reflecting limitations of other abilities involved in ToM tasks (e.g. inhibition). Special circumstances such as early bilingualism may enhance ToM development or other capacities required by ToM tasks. Here we compare 3-year-old bilinguals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
176
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(192 citation statements)
references
References 43 publications
11
176
2
3
Order By: Relevance
“…Furthermore, the general language competence and working memory of all participants may have influenced the results and would be useful to include in a future study. For example, according to previous research (Bialystok, 1999;Kovacs, 2009), ToM should be explored in various cultural contexts in which children speak more than one language because the ability to speak more thank one language may influence ToM performance directly and indirectly (via better executive function in bi-and multilinguals).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the general language competence and working memory of all participants may have influenced the results and would be useful to include in a future study. For example, according to previous research (Bialystok, 1999;Kovacs, 2009), ToM should be explored in various cultural contexts in which children speak more than one language because the ability to speak more thank one language may influence ToM performance directly and indirectly (via better executive function in bi-and multilinguals).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, cognitive control or executive functions (EF) refer to mechanisms involved in conflict monitoring, planning, attentional control, and the suppression (inhibition) of habitual responses (13,14). Previous research has shown that the habitual use of 2 languages leads to improved cognitive control in young and older adults and in preschool and school-aged children (15)(16)(17)(18). This improvement is generally attributed to the need of bilinguals to inhibit one language while switching to the other language in production (12,19).…”
mentioning
confidence: 99%
“…Theory of Mind studies have revealed that 3-year-old bilinguals outperform monolingual children of the same age in standard FB tasks (Goetz, 2003;Berguno & Bowler, 2004;Kovács, 2009Kovács, , 2012Nguyen & Astington, 2014;Gordon, 2016; see also Bialystok & Senman, 2004;Greenberg et al, 2013), and parallel results have been reported with bilingual adults (Rubio-Fernández & Glucksberg, 2012). These studies discuss a number of experiential factors that could boost bilinguals' understanding of false belief, such as having greater metalinguistic awareness (e.g.…”
Section: Bilinguals Outperform Monolinguals In Fb Tasksmentioning
confidence: 50%
“…In contrast, according to competence accounts, the bilingual experience should give bilingual children an advantage in the modified FB task (which was set up in the kind of language-switch scenario that bilingual children regularly experience) but not in the standard FB task. As predicted by the performance accounts, the 3-year-old bilinguals in Kovács (2009) outperformed their monolingual peers in both types of task.…”
Section: Bilinguals Outperform Monolinguals In Fb Tasksmentioning
confidence: 60%
See 1 more Smart Citation